Key attributes of Muslim-friendly hotels' service quality: voices from booking.com - Arasli, Huseyin; Saydam, Mehmet Bahri; Gunay, Tugrul; Jafari, Kaveh (Emerald Group Publishing Ltd, 2023)
Purpose On a global scale, the Muslim-friendly hospitality business has intensified hotel competition. Given the paucity of research on the important service quality characteristics of Muslim-friendly hotels, this study aims to identify the major themes encountered by tourists at Muslim-friendly hotels. Design/methodology/approach The research used content analyzes (qualitative) to examine 1,250 reviews using Leximancer software. Data were gathered from the online travel website booking.com. The top 10 Islamic hotels according to Crescent ranking were taken into a data set. Findings Qualitative (narratives) analysis showcased nine key themes, namely, hotel, staff, food, room, location, pool, facilities, cleanliness and Wi-Fi. Furthermore, the findings of this study contribute to filling research voids in the literature by distinguishing themes linked with halal hotel satisfaction from those associated with dissatisfaction. Originality/value The findings of this research offer valuable visions into halal-hotel travelers' overall experiences based on user-generated content and facilitate the identification of the dominant themes linked with a different value for money ratings.
Keywords: Service quality; Content analysis; Hotel industry; Web reviews; Satisfaction; Leximancer